Rebellion Against The Unjust Authority Reflected In Suzanne Collins' Mockingjay (2010): Sociological Criticism - Cahyaningrum, Rika, Dr. M. Thoyibi, M.S, Siti Fatimah, S. Pd, M. Hum (2014)
This research paper elaborates the rebellion against the unjust authority reflected in Suzzanne Collins that are analyzed through the sociological approach. The objectives of the research are to analyze the structural elements of the novel and to analyze the novel based on the sociological approach.This research belongs to a descriptive qualitative research. The data of the research is the novel entitled Mockingjay. The data source comes from both primary data source which is in the form of the text of the novel which is being researched and secondary data source such as biography of the author, websites and other sources. The method to analyze the data is descriptive analysis. Having analyzed the novel, the researcher comes to the conclusions as follows: from the structural elements of Mockingjay novel, the writer finds that in this novel, the author wants to deliver a message that power abuse may result in rebellion. In order to deliver the message, the author creates the characters that abuse the power and those that struggle against the power abuse. From sociological approach, it is evident that in this novel, the author reflects the social realities of the American social at the beginning of the twenty-first century. The author also criticizes the tendency of the government to abuse power.